Capturing the sustainability features that most affect consumer evaluations case: mobile phones. Issue 4 (2nd October 2018) - Bask, Anu; Halme, Merja; Kuula, Markku
ABSTRACT: A product's sustainability affects its consumer evaluation. Sustainable supply chain management (SSCM) research emphasizes the customer role, but typically adopts the company view. On the other hand, when consumer choice is studied, sustainability is mostly evaluated in terms of one feature only, instead of the many facets of sustainability. This research gap has been filled in this study by broadening the view of SSCM to encompass how the consumer relates to different features of sustainability. SSCM literature is first used to construct a conceptual framework for consumer product evaluations and to provide a basis for focus group discussions aimed at identifying the different sustainability features. The case product (mobile phones) has high volumes and short lifecycles that affect environmental sustainability. In our focus group results, all framework themes were present with varying importance. The groups unanimously wished to extend the lifecycle of the phones, an observation affecting product design. A strong demand for information sharing related to supplier management and recycling was also discovered.